Basmajian-type inequalities for maximal representations - Fanoni, Federica; Pozzetti, Maria Beatrice (Journal of differential geometry, 2020)
For suitable metrics on the locally symmetric space associated to a maximal representation, we prove inequalities between the length of the boundary and the lengths of orthogeodesics that generalize the classical Basmajian’s identity from Teichmüller theory. Any equality characterizes diagonal embeddings.